Law applicable to international employment contracts: prohibition of «pick and choose» (The decision of the Higher Court of Madrid of March 24, 2018) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The decision at issue in this study constitutes an example of rigor and precision in the application of the private international law system on work. The Court analyzes both the question of the law applicable to the employment contract ant that of the proof -or lack of it- of foreign law, as a result of a wage claim of some workers at the service of the Ministry of Foreign Affairs. The Court shows in both subjects a solid knoweledge of the rules of private international law and its interpretative doctrine, of which he makes a didactic presentation and very correct application. This analysis leads him to criticize the legislative division of the contract, when it is not justified, naming it as «pick and choose».